Impact of climate change on Meteorological drought in Insana Barat District, Timor Tengah Utara, East Nusa Tenggara - Maria Serlince Sanit; Turningtyas Ayu Rachmawati; Nailah Firdausiyah (Syntax Literate, 2023)
Uncertain climate change has an impact on the limited availability of surface water and low rainfall, causing Insana Barat District to become one of the areas prone to drought. Drought is a cause of poverty because it is usually associated with the cycle and spread of disease and threats to food security. Therefore, it is necessary to identify drought characteristics in this region for early anticipation and adaptation to reduce the impact of drought due to current and future climate variability. The Standardized Precipitation Index (SPI) is an index used to determine the deviation of rainfall from normal over a long period. The SPI method was chosen because of its ability to calculate the index and describe the severity of drought, and it is simpler than other methods. The advantage of SPI is that it is sufficient to use monthly rainfall data to compare drought levels between regions even with different climate types. The data used in this study is rain data from rain stations located in Insana Barat District from 2007 to 2021. The results show that in the drought deficit period the deficit period is 3 months in 2021 with an index value of -5.123. The worst 6-month deficit period for the -4,458 index occurred in 2020. The worst 12-month drought index deficit period of -2,191 occurred in 2021.